1998
DOI: 10.3109/03005364000000049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Noise Induced Hearing Loss with Distortion Product Otoacoustic Emissions

Abstract: This study assessed the clinical efficacy of screening for noise induced hearing loss (NIHL) with distortion product otoacoustic emissions (DPOAE). DPOAEs were recorded from 76 military personnel (137 ears) aged between 17 and 41 years in response to equilevel 70 dB SPL primary stimulating tones. The 2f1-f2 DPOAE levels were correlated with audiometric thresholds at frequencies close to f2. Ears with normal audiograms, but with a history of military noise exposure, had DPOAEs that were significantly decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 19 publications
1
28
0
2
Order By: Relevance
“…Several cross-sectional studies have been performed that have provided evidence for the effect of noise on OAEs. (Lepage & Murray 1993, Desai et al, 1999Attias et al, 1998).…”
Section: Discussionmentioning
confidence: 97%
“…Several cross-sectional studies have been performed that have provided evidence for the effect of noise on OAEs. (Lepage & Murray 1993, Desai et al, 1999Attias et al, 1998).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, noise-exposed people tend to have lower OAEs than people with similar audiometric thresholds but no noise exposure ͑Bicciolo et Murray and LePage 1993;Attias et al, 1995Attias et al, , 1998Xu et al, 1998;Desai et al, 1999;Attias et al, 2001͒. 1 This finding has led to the hypothesis that, in individuals, OAEs may decrease prior to changes in audiometric thresholds.…”
Section: Introductionmentioning
confidence: 92%
“…Recently, a number of studies have demonstrated that distortion product otoacoustic emission (DPOAE) is more sensitive than the traditional hearing test in revealing the acute effects of noise [21,22]. Therefore, in addition to the ABR threshold measures, we also employed DPOAE measures to assess the effects of noise exposure in experimental animals.…”
Section: Introductionmentioning
confidence: 99%